2021
DOI: 10.1177/0739456x211021151
|View full text |Cite
|
Sign up to set email alerts
|

Competing in the Planning Marketplace: An Analysis of Qualifications Demanded by Municipal Planning Recruiters

Abstract: This study sought to understand the knowledge, skills, qualities, and tasks that municipal employers expect from planners and to assess how well they align with those identified as important by academic scholars and accreditation bodies. Through a content analysis of 150 municipal planning employment advertisements collected from across Canada, the study identified the planning-relevant qualifications demanded by municipal governments. The analysis revealed that the municipal planning sector prefers prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Also, while systematic research is lacking, a recent study is suggestive. A survey of recruitment ads for Canadian municipal planners (Guyadeen and Honsta, 2021) found desired knowledge areas to include official plan and zoning bylaw amendments, subdivision and site planning and processing plan applications, and recommendations and advice on land use, development control, and planning studies among assigned tasks. These demands clearly identify municipal planning with a recognized knowledge-centered practice: spatial, urban or city, and regional planning.…”
Section: Discussionmentioning
confidence: 99%
“…Also, while systematic research is lacking, a recent study is suggestive. A survey of recruitment ads for Canadian municipal planners (Guyadeen and Honsta, 2021) found desired knowledge areas to include official plan and zoning bylaw amendments, subdivision and site planning and processing plan applications, and recommendations and advice on land use, development control, and planning studies among assigned tasks. These demands clearly identify municipal planning with a recognized knowledge-centered practice: spatial, urban or city, and regional planning.…”
Section: Discussionmentioning
confidence: 99%
“…"Little to no evidence" Accreditation of degrees is managed by either the Planning Accreditation Board (a separate organization from the American Planning Association membership society) or the quasi-affiliated credentialing organization AICP (Planning Accreditation Board 2006;Roach 2015). Confusion and disagreement over the core professional identity (Davoudi and Pendlebury 2010; Edwards and Bates 2011) contribute to numerous problems in the profession, including a growing divide between applied practice and the increasingly theoretical academic discipline (Goodman et al 2022), encroachment into planning by other professions (Myers and Banerjee 2005), and the lack of a consistently applied BoK (Dawkins 2016;Miller 2019;Guyadeen and Henstra 2021), which all taken together leave the future of the planning profession unclear.…”
Section: Pit Operationalization: Compare the Urban Forestry Professio...mentioning
confidence: 99%
“…In other professions, such as planning, membership with the Canadian In stitute of Planners and its professional planning designation is promoted heavily. Guyadeen and Henstra (2021) found that roughly 80 percent of planning employ ment advertisements sought recruits with membership in the Canadian Institute of Planners or respective provincial planning chapters. Moreover, most postings demanded that candidates possess or be in pursuit of offi cial Registered Profes sional Planner designation.…”
Section: Promoting the Value Of The Ce Designationmentioning
confidence: 99%